Long-Term Viruria in Zika Virus-Infected Pregnant Women, Brazil, 2016 - Terzian, Ana Carolina B.; Estofolete, Cassia Fernanda; Silva, Rafael Alves da; Mos Vaz-Oliani, Denise Cristina; Oliani, Antonio Helio; Brandao de Mattos, Cinara Cassia; Mattos, Luiz Carlos de; Rahal, Paula [UNESP]; Nogueira, Mauricio L. (Centers Disease Control, 2017)
During the 2016 Zika virus outbreak in Brazil, we detected Zika virus RNA in urine samples collected from Zika virus-positive pregnant women during different stages of pregnancy. Women had positive and negative intervals of viruria; 3 newborns had adverse outcomes. Further research is needed to clarify the relationship between viruria and outcomes for newborns.